Cues Matter: Learning Assistants Influence Introductory Biology Student Interactions during Clicker-Question Discussions - Knight, Jennifer K. (CBE Life Sci Educ, 2015)
The cues undergraduate biology instructors provide to students before discussions of clicker questions have previously been shown to influence student discussion. We further explored how student discussions were influenced by interactions with learning assistants (LAs, or peer coaches). We recorded and transcribed 140 clicker-question discussions in an introductory molecular biology course and coded them for features such as the use of reasoning and types of questions asked. Students who did not interact with LAs had discussions that were similar in most ways to students who did interact with LAs. When students interacted with LAs, the only significant changes in their discussions were the use of more questioning and more time spent in discussion. However, when individual LA–student interactions were examined within discussions, different LA prompts were found to generate specific student responses: question prompts promoted student use of reasoning, while students usually stopped their discussions when LAs explained reasons for answers. These results demonstrate that LA prompts directly influence student interactions during in-class discussions. Because clicker discussions can encourage student articulation of reasoning, instructors and LAs should focus on how to effectively implement questioning techniques rather than providing explanations.